(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of the research entitled “the development of intensive English research writing training model to encourage international publishing for university lecturers” were to: 1) develop intensive English research writing training model to encourage international publishing for university lecturers and to assess the effects of the use of intensive English research writing training model as following methods: 1) to assess English writing skill about research for international publishing, 2) to assess research competency of university lecturers, 3) to assess the language lecturers’ satisfaction towards intensive English research writing training model, 4) to assess the research full paper’s quality of the university lecturers, and 5) to follow up efficiency of university lecturer’s research from a number of researches published in an international conference or a journal. The population was 42 university lecturers at College of General Education and Languages, Thai-Nichi Institute of Technology, Bangkok, Thailand. The samples were 17 language lecturers derived through volunteer random sampling techniques. The research instruments comprised of tests, questionnaire, interview forms, and assessment forms. Data were analyzed in terms of percentage, means, standard deviation, t-test, and content analysis. Research findings were found as follows: 1) the intensive English research writing training model to encourage international publishing for university lecturers was proved to be effective and verified as by experts. 2) The empirical data that supported the effectiveness of the intensive English research writing training model were as follows: 1) regarding to the university lecturers, their English writing skill about research for publishing in international conference before and after the implementation of the intensive English research writing training model were statistically significant different at the .05 level; 2) The research competency of university lecturers also demonstrated a high level of competency on research; 3) They were satisfied with the intensive English research writing training model at the highest level; 4) Regarding to the quality of research full paper, it was found that a number of research full papers which were verified from experts were at a good level; and 5) Regarding to follow up efficiency of university lecturer’s research from a number of research published in an international conference, it was found that there were 17 research papers (out of 17) which were published in international conference after the implementation of the intensive English research writing training model.